Phase 0 Radiopharmaceutical–Agent Clinical Development - Kunos, Charles A.; Rubinstein, Larry V.; Capala, Jacek; McDonald, Michael A. (Frontiers in Oncology, 2020)
The evaluation of antibody-targeted or peptide-targeted radiopharmaceuticals as monotherapy or in oncological drug combinations requires programmatic collaboration within the National Cancer Institute (NCI) clinical trial enterprise. Phase 0 trials provide a flexible research platform for the study of radiopharmaceutical-drug pharmacokinetics, radiation dosimetry, biomarkers of DNA damage response modulation, and pharmacodynamic benchmarks predictive of therapeutic success. In this article, we discuss a phase 0 clinical development approach for human antibody-targeted or peptide-targeted radiopharmaceutical-agent combinations. We expect that early-phase radiopharmaceutical-agent combination trials will become a more tactical and more prevalent part of radiopharmaceutical clinical development in the near-term future for the NCI Cancer Therapy Evaluation Program.